Assessment of the Circular Economy’s Impact in the EU Economic Growth - Mariana Vuță; Mihai Vuţă; Adrian Enciu; Sorin-Iulian Cioacă (Amfiteatru Economic)
Starting from the significant differences between the European Union’s member states regarding framing and implementing the sustainable development strategies and the transition from linear economy towards circular economy (European Commission, 2017a), the article analyses the impact that circular economy indicators, such as the recycling rate of municipal waste, packaging waste and bio-waste, the expenditure on research and development to find solutions to extend the life cycle of materials and reusing waste, as well as the environmental taxes have on the resource productivity and real economic growth. Using these correlations, we consider that the transition from the linear economic model to the circular economic model has positive effects, as proven by this study. The proposed model uses data for the 28 member states of the European Union, in the 2005-2016 time frame. The novelty of this study lies in using a data panel model for estimating the impact that the measures associated with the circular economy have on the resource productivity and economic growth. The obtained results show that the resource productivity improves by 0.01307 considering one percent increase in the recycling rate of the municipal waste, by 0.159988 if the research and innovation as percentage in the GDP increases by one percent and by 0.068711 when the number of patents in the EU (as for 1 million inhabitants) increases by one unit. All these values stress out the positive effects the circular economy model may have on the society’s sustainable development.